The impact of touch restrictions in small-sided games on soccer players' passing, receiving, and ball-touch temporal intervals - Rosten, M.; Aune, T. K.; Dalen, T. (Journal of Human Kinetics, 2025)
The present study aimed to investigate how players` technical actions were influenced by different touch restrictions in small-sided games (SSGs). Specifically, it analysed differences in the temporal intervals separating players' first and second touches across varied field zones—defensive, centre, and offensive—in SSGs. The experimental design involved twelve male junior soccer players playing under three distinct 4v4 SSG conditions: 1) a maximum of two touches per player; 2) a maximum of three touches per player; and 3) unrestricted play with no touch restrictions. Ten games of 4v4 SSGs (4 players + goalkeeper per team) were held for each condition, resulting in a total of 30 games of 4v4 SSGs investigated across eight distinct test sessions. Players had the shortest intervals between their first and second touches in the offensive zone, followed by the centre and then the defensive zones. Furthermore, the imposition of touch restrictions in SSGs led to a heightened frequency of passes compared to SSGs characterised by unrestricted gameplay; by contrast, SSGs featuring free play facilitated a greater number of receptions compared to SSGs with constraints on the number of touches. In conclusion, the current study outlines distinct differences in temporal intervals between the first and second touches of the ball across distinct field zones, notably showcasing a significant reduction in the time elapsing between touches as players neared their opponents` goal.